Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Modifikasi Terbimbing Siswa Kelas Viii MTs Swasta Nurul Iman Kecamatan Hinai - Fatimah Ahmad; Diani Syahfitri; Tri Aulia (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
Efforts to improve student learning outcomes through a modified learning model guided by class VIII MTs. Private Nurul Iman Hinai District. The subjects of this study were students of class VIII MTs. Private Nurul Iman, Hinai District, totaled 30 people. This study uses the classroom action research method with 4 stages commonly used in classroom action research, namely planning, implementation, observation, reflection which are summarized in cycles and in this study carried out in cycle II. As for the results of teaching and learning activities in the initial observation there are still learning outcomes that have not been maximized. In the first cycle there were research results of students who achieved learning mastery individually as many as 19 students or 63%, while 11 students or 37% had not achieved learning mastery. While in the second cycle with the results of 100% students achieve complete learning individually and are able to express opinions in discussions and analyze the problems they face and are able to solve them well. From the results of the study, it can be concluded that the use of guided modified learning models in the learning process can improve student learning outcomes for class VIII MTs. Private Nurul Iman Hinai District.